2021
DOI: 10.21203/rs.3.rs-339830/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Calcium Peroxide Promoted Anaerobic Co-digestion of Plant Waste and Excess Sludge to Produce Methane

Abstract: Plant waste (PW) and excess sludge (ES) are two main organic matters of municipal solid waste. However, there are few reports on their anaerobic co-digestion. In this work, the mixed proportion of PW and ES anaerobic co digestion was first optimized at mesophilic temperature, and then the anaerobic co-digestion of PW and ES was enhanced with strong oxidant calcium peroxide (CP). The results showed that the optimal mixing ratio of PW and ES was 1/1 (in terms of volatile solids), and the C/N of mixed digestion s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Qiuying Huang [19] studied a co-fermentation method to improve the gas production performance of rice straw and obtained the same results. In order to construct an efficient and stable rice straw sludge with a combined anaerobic digestion system, Yiran Wang [20] conducted a batch experiment of combined anaerobic digestion using different types of rice straw and excess sludge. The research results showed that the addition of rice straw significantly increased the methane content compared to the single anaerobic digestion of sludge.…”
Section: Introductionmentioning
confidence: 99%
“…Qiuying Huang [19] studied a co-fermentation method to improve the gas production performance of rice straw and obtained the same results. In order to construct an efficient and stable rice straw sludge with a combined anaerobic digestion system, Yiran Wang [20] conducted a batch experiment of combined anaerobic digestion using different types of rice straw and excess sludge. The research results showed that the addition of rice straw significantly increased the methane content compared to the single anaerobic digestion of sludge.…”
Section: Introductionmentioning
confidence: 99%